THE ROLE OF ADJECTIVES IN THE SECOND LANGUAGE (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This research aims to analyze the types of adjectives and their functions, grammatical, syntactical and morphological categories and characteristics.